De Novo Small Supernumerary Marker Chromosomes Arising From Partial Trisomy Rescue - Matsubara, Keiko; Yanagida, Kaede; Nagai, Toshiro; Kagami, Masayo; Fukami, Maki (Frontiers in Genetics, 2020)
Small supernumerary marker chromosomes (SMCs) are rare cytogenetic abnormalities. De novo small SMCs, particularly those combined with uniparental disomy (UPD), are assumed to result from incomplete trisomy rescue. Recently, a one-off cellular event designated as chromothripsis was reported as a mechanism for trisomy rescue in micronuclei. This Perspective article aims to highlight a possible association among trisomy rescue, chromothripsis, and SMCs. We propose that chromothripsis-mediated incomplete trisomy rescue in micronuclei underlies various chromosomal rearrangements including SMCs, although other mechanisms such as U-type exchange may also yield SMCs. These assumptions are primarily based on observations of previously reported patients with complex rearrangements and our patient with a small SMC. Given the high frequency of trisomic cells in human preimplantation embryos, chromothripsis-mediated trisomy rescue may be a physiologically important phenomenon. Nevertheless, trisomy rescue has a potential to produce UPD, SMCs, and other chromosomal rearrangements. Overall, we provide novel insights into the mechanism for the maintenance and modification of human chromosomes.